MENGGALI NILAI-NILAI KEUNGGULAN LOKAL KESENIAN REOG PONOROGO GUNA MENGEMBANGKAN MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA PADA MATA PELAJARAN IPS KELAS IV SEKOLAH DASAR - Imam Gunawan; Rina Tri Sulistyoningrum (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
Value from a culture nation inheritance is very important. Local wisdom a region contains values necessary exploration and preserved. Reog is one of the artistry enough famous from region Ponorogo and known by world society. Values found in artistry Reog Ponorogo presumably necessary are exploration furthermore to can be ingredient for tribe unity matter development and culture in course social science class IV elementary school. With artistry local superiority values implementation existence Reog Ponorogo, supposed student realizes and apply values from region culture permanently respect coalitions taste and sense of belonging towards region culture. This research aims to detect artistry local superiority values Reog Ponorogo that is used to develop tribe unity matter and culture course elementary school. Research data collecting is done gradually that is passes documentation study, observation, and interview. Technique that done gradually (triangulating) this chosen to guarantee data validity. Data is fished from informant that chosen with snowball sampling technique. Taking manner sampling with this technique is done according to related to, sample determination technique at first number little, longer more expand. In first research at first is chosen one or two person but because data to felted not yet enough so researcher looks for another person that can equip data that got from previous person. These research results show that artistry local superiority values Reog Ponorogo can be used to develop tribe unity matter and subject culture social science Class IV elementary school that is: leadership, aesthetics, and agreement.